Antipyretic activity test of papaya leaf extract (Carica papaya L.) against peptone-induced male white mice - Mayqhuellia, Marsyanda Happy; Hayu Widyasti, Jena (Surya Hijau Manfaat, 2024)
Fever increases body temperature above normal (98.6°F/ 37°C). To treat complaints of fever, antipyretic drugs are given. Papaya leaves are believed to have antipyretic effects. The purpose of this study was to test the antipyretic activity and effective dose of ethanol extract of papaya leaves (Carica papaya L.) against peptone-induced mice. The test animals were grouped into 5 groups consisting of group I (negative control) CMC Na 0.5%, group II (positive control) paracetamol drug 65 mg/KgBB mice, group III papaya leaf ethanol extract 140 mg/KgBW mice, group IV papaya leaf ethanol extract 280 mg/KgBW mice, and group V papaya leaf ethanol extract 560 mg/KgBW mice, with peptone fever inducer 10 mL/kgBW subcutaneously. The body temperature of the test animals was observed every 30 minutes for 240 minutes after peroral administration of the preparation, then obtained data on T0, Tdemam and body temperature measurements at each time. The data was then used to calculate the AUC and the average AUC calculation data was analyzed by Shapiro wilk test and One way Anova test. The results of the study of ethanol extract of papaya leaves have antipyretic effects, namely due to the presence of flavonoids, alkaloids, tannins, steroids, and saponins. Papaya leaf ethanol extract has the most effective antipyretic activity, namely a dose of 560 mg/kg BW, which is comparable to the positive control of paracetamol.